Meeting the challenges in conducting research in vulnerable older adults with self-neglect-notes from a field team - Pickens, Sabrina; Burnett, Jason; Trail Ross, Mary Ellen; Jones, Erick; Jefferson, Felicia (Frontiers in Medicine, 2023)
Gaining an understanding of the interventions that may be successful in increasing the lifespan of vulnerable older adults with self-neglect often presents with barriers. Many of these challenges are directly related to identifying and maintaining contact with patients in the community. Discussion of these overarching challenges as experienced in interactions with patients throughout various research studies in older adults with self-neglect are presented. Two potential solutions are proposed.